PROSPEK PERDAGANGAN KOPI ROBUSTA INDONESIA DI PASAR INTERNASIONAL - Devi Chandra; R. Hanung Ismono; Eka Kasymir (Lampung University, 2013)
This research aims to predict the trades of Indonesian coffee in the international market for the next decade.This research used secondary data, specifically the export volume of robusta coffee from 1975 to 2011.Forecasting process was done by using the method of linear time series analysis with ARIMA models. Theresults showed that the model for maximum export volume of robusta coffee was Yt = Yt-1 + 6.646 – 0.5028(Wt-1 – Wt-2) – 0,4134 (Wt-2 – Wt-3) + et.. It was predicted in the next 10 years, from 2012 to 2021, the exportvolume of the Indonesian coffee will increase. The growth of the export volume of robusta coffee will be1.6% each year. Finally, in 2021 the export volume of robusta coffee will reach 493.295 tons.